Reflective feedback practices and their expressions of inequality in times of pandemic - Chura-Cutipa, Luz M. (2021)
This article explain the difference between "reflective feedback practices" in times of pandemic, based on inequality in access to virtual tools synchronously and asynchronously, on the form of reflective feedback that teachers perform with new and different applied digital strategies to achieve learning. The objective was to analyze the feedback from the teacher's point of view and its importance in the development of reading skills. The applied methodology was qualitative, by means of a phenomenological design, using the technique of interviewing with a guide that consigned a series of questions around our study categories. The results show that feedback is possible through synchronous and asynchronous teaching, which are worked from the group development of the students and from their evidence, which influence the improvement of reading skills. In addition, the technological limitations of connectivity and accessibility show, during the pandemic (COVID-19), an inequality in the feedback, favoring those who had a synchronous learning, concluding that a good relationship is established between the variables studied and that gets an improvement despite economic adversities.